Infarcts in the territory of the lateral branch of the posterior inferior cerebellar artery. Issue 9 (September 1994) - Barth, A; Bogousslavsky, J; Regli, F
Abstract : The territory of the lateral branch of the posterior inferior cerebellar artery (1PICA) supplies the anterolateral region of the caudal part of the cerebellar hemisphere. Because infarcts in the territory of the 1PICA have rarely been studied specifically, 10 patients with this type of infarct are reported. An 1PICA infarct was isolated in only three patients, whereas it was associated with brainstem infarct in four, with occipital infarct in one, and with multiple infarcts in two patients. The most common symptom at onset was acute unsteadiness and gait ataxia without rotatory vertigo (six patients). Unilateral cerebellar dysfunction was found in all patients, with limb ataxia (nine patients), dysdiadochokinesia (five patients), and ipsilateral body sway (four patients), but dysarthria and primary position nystagmus were notably absent. In the patients with a coexisting infarct in the brainstem, cranial nerve and sensorimotor dysfunction was prominent and often masked the signs of cerebellar dysfunction. Unlike other infarcts in the PICA territory, 1PICA territory infarcts were mainly associated with vertebral artery atherosclerosis (six patients), whereas cardiac embolism was less common (three patients). Unilateral limb ataxia without dysarthria or vestibular signs suggests isolated 1PICA territory infarction and should allow its differentiation from other cerebellar infarcts.